Religion and the Making of Nigeria - Vaughan, Olufemi (Book collections on Project MUSE., 2016)
In Religion and the Making of Nigeria Olufemi Vaughan examines how Christian, Muslim, and indigenous religious structures along with the legacies of British colonial rule have provided the essential social and ideological frameworks for the construction of contemporary Nigeria.